Human papillomavirus DNA and p16 expression in head and neck squamous cell carcinoma in young French patients. Issue 7 (July 2021) - Molimard, Chloé; L'Huillier, Virginie; Overs, Alexis; Soret, Christine; Algros, Marie-Paule; Mougin, Christiane; Guenat, David; Mauvais, Olivier; Prétet, Jean-Luc
Objectives: Human papillomavirus (HPV) is a risk factor for head and neck squamous cell carcinoma (HNSCC), which is currently increasing worldwide. We evaluated the prevalence of HPV DNA and p16 expression in HNSCC patients age <45 years compared with patients aged ≥45 years. Methods: Thirty-nine patients aged <45 years who presented at Besançon University Hospital with HNSCC since 2005 were included in this retrospective study. HPV DNA was detected by HPV genotyping and p16 expression was determined by immunohistochemistry using paraffin-embedded tissues. A matched-group of 38 patients aged ≥45 years from Besançon University Hospital was included. Results: The overall prevalence of HPV infection was 11.7%. HPV16 was the only genotype detected in 4/39 and 5/38 patients, and p16 was expressed in 6/39 and 4/38 patients aged <45 years and ≥45 years, respectively. Conclusions: HPV-positivity and p16 expression were similar in both age groups. The results suggest that p16 immunohistochemistry may provide a prognosis biomarker for all HNSCCs, not only oropharyngeal cancers, and this should be addressed in large clinical trials.